The Value of Arts-Based Methods in STEM: Formal Analysis, Open Dialogue, and Subjectivity - Smylitopoulos, Christina; Mousseau, Sarah; Byrne-Mamahit, Nakita; Oatley, Sarah; Sutton, Anna (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2024)
In the Fall of 2021, STEM researchers were invited to participate in a series of SSHRC-funded workshops delivered at the University of Guelph’s School of Fine Art and Music (SOFAM), where they examined a work of abstract art drawn from the SOFAM Print Study Collection (Reflex Victory by Chrysanne Stathacos, lithograph, 1979). The project’s objective was to determine if methodologies used in the analysis and interpretation of art are helpful to researchers who use visual observation as a primary method of collecting data. Our findings indicate that over the duration of the one-hour workshop, participants demonstrated greater confidence in identifying what lay in their fields of vision with precision, exhibited greater comfort in pursuing open-ended inquiry, and became more conscious of the mutable and subjective qualities of their looking. This report shares the story of our experiment and presents our preliminary findings on the value of arts-based methodologies in developing skills in data collection and analysis. This research contributes to the discourse on the role visual art can play in practices of teaching, learning, and research that extend beyond the studio, museum, and gallery space.